Modulaciones de la ciudad en la ficción televisiva contemporánea - Cappello, Giancarlo (2023)
This article deals with the representation of urban space in television fiction through an approach that, starting from the works around the moving image and its modes of production, incorporates contributions from critical studies on cities. Through a content analysis that involves 10 successful series, the text distinguishes three modulations: one where the city and its meaning are built by appealing to the previous cultural conditions of the place from historical events and difficult legacies to issues settled by picturesqueness, tourism or popular tradition; another where the elements and characteristics of the location are exploited, conveniently amplifying, attenuating or retouching its different edges in favor of the story; and a third that appeals directly to the viewer and his background to bring ideas or external realities closer to the work itself and produce a dialogue between texts. It is concluded that the soap operas face the space as a persuasive, functional and aesthetic action that, by making use of their performative practices, turn the city into a landscape that reveals a different and more phenomenological understanding of urban daily life.